Kadar Protein dan Zat Besi Churros Dengan Substitusi Tepung Daun Kelor Dan Tepung Ikan Teri Tawar - Adriyani Adam; A. Tia Mutiara Ihsan; Retno Sri Lestari; Fatmawati Suaib (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Teenage girls are a group that is vulnerable to anemia due to low iron intake in their daily diet. According to data from the Health Department of Makassar City, the prevalence of anemia among adolescent girls reached 3.98% of the total 4,788 individuals. To date, anemia prevention efforts have primarily focused on iron supplements. However, this approach often faces challenges such as low compliance rates with supplement intake, gastrointestinal side effects, and a lack of practical nutrition education. Therefore, an innovative and sustainable strategy is needed through a functional food approach based on local resources. One potential alternative snack food is churros, a light snack that can be enriched with moringa leaf flour and anchovy flour as natural sources of protein and iron. This study aims to analyze the protein and iron content in churros products formulated with moringa leaf flour and anchovy flour substitutes. This study used a pre-experimental design with a post-test only design. The study was conducted at the Makassar Health Laboratory Center. Protein content was tested using the Micro Kjeldahl method, and iron content was analyzed using Atomic Absorption Spectrophotometry (AAS). The results showed that the protein content in churros was 0.4186 grams per 4 grams of sample, equivalent to 10.465 grams per 100 grams. The iron content reached 0.1704 mg per 4 grams or 4.26 mg per 100 grams of product. It is recommended that further research focus on optimizing the processing to maintain protein quality and analyzing other nutrient contents as part of the development of local functional food-based churros products. Keywords: Churros, protein, iron